Becoming an insectivore: Results of an experiment. (July 2016) - Hartmann, Christina; Siegrist, Michael
Highlights: Next to food neophobia, living food contaminants disgust leads to low willingness to eat insects. People are willing to consume processed insect products. People who have consumed processed insect products are more willing to eat unprocessed insects. Processed insect foods may pave the way for acceptance of insects in the daily diet. Abstract: In many parts of the world, people consume insects due to their nutritive value and low environmental production costs. However, Western societies rarely experience insects as a food source. To overcome initial resistance, researchers have suggested introducing insects into the market in a processed form so that those characteristics which are repellent to Western consumers are no longer readily visible. Thus far, the success of this strategy is untested. For the present experiment, we used two kinds of tortilla chips. One was made with a traditional corn flour recipe, while the other included cricket flour as an ingredient. People from the general population ( N = 104) were randomly assigned to consume either the traditional chips (control condition) or the cricket chips (experimental condition). After answering questions related to their eating behaviours, the participants tasted the chips. Both groups were informed prior to the tasting what kind of chips they would be sampling. After the tasting, the participants were questioned again to assess their willingness to eat unprocessed insects. Multiple linear regression showed that the experimental condition ( β = .16) had a significant effect on willingness to eat unprocessed insects, while simultaneously controlling for the impact of previous insect consumption ( β = .36), food neophobia ( β = −.33) and animal-based food contamination disgust ( β = −.17). People in the experimental condition reported a higher willingness to eat unprocessed insects than people in the control condition. The present experiment showed that exposure to processed insect products can increase consumers' willingness to consume unprocessed insects.